Method for recycling rare earth in waste polishing powder through mechanochemical enhanced deconstruction and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs
Through mechanochemical strengthening deconstruction technology, acid leaching extraction and salt precipitation technology, waste polishing powder is efficiently recovered by waste polishing powder, and catalysts are prepared by template method for VOCs degradation, which solves the problems of complex processes and high energy consumption in the existing technology, and realizes efficient recycling and high-quality recycling of rare earth elements.
Patent Information
- Application Number
- CN202510013059.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-06
AI Technical Summary
In the prior art, the recycling process of rare earth elements in waste polishing powder is complex, the chemical reagents consume largely, the water and energy consumption are high, and the recycling cost is high.
Mechanical chemical reinforced deconstruction technology is used to pretreat waste polishing powder to change the structural stability of rare earth components and make it easy to leaching. Then, the high-efficiency separation and purification of rare earth elements was carried out by combining acid leaching extraction and complex salt precipitation technology, and finally the La2O3/CeO2 catalyst was prepared by the template method for efficient catalytic degradation of VOCs.
It realizes efficient recycling and high-quality recycling of rare earth elements in waste polishing powder, with mild process conditions, high economic benefits and strong universality, reducing environmental pollution and recycling costs.
Smart Images

Figure CN119857475A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of valuable metal recovery and high-quality utilization in solid wastes, and in particular to a method for recovering rare earths in waste polishing powder by mechanochemical enhanced deconstruction and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs. Background Art
[0002] As an important strategic metal resource, rare earth elements play a vital role in clean energy, environmental protection, military and other fields with the continuous progress of science and technology and industry. With the continuous increase in demand for rare earths, especially in optoelectronics, magnetic materials and catalysts, the sustainable utilization of rare earth resources has become increasingly prominent. However, the mining of rare earth ore resources is not only costly, but also puts great pressure on the ecological environment. Therefore, how to recycle rare earth elements in solid waste resources and achieve their efficient reuse has become an important issue to be solved. Waste polishing powder, as a by-product of the electronics, optics and mechanical processing industries, has become an important source of rare earth recovery in solid waste resources. Waste polishing powder is rich in rare earth elements, especially lanthanide elements such as lanthanum and cerium. Therefore, the recovery and reuse of rare earth elements in waste polishing powder can not only reduce the waste of rare earth resources and generate certain economic benefits, but also replace primary mineral resources to a certain extent and reduce the environmental burden brought by raw ore mining. In addition, volatile organic compounds (VOCs) are the main precursors of atmospheric pollutants. In order to improve air quality, the emission control of VOCs is particularly urgent. Rare earth-based catalysts have shown obvious advantages in catalytic degradation of VOCs and their reaction selectivity. Based on this background, the recovery of rare earths in waste polishing powder and its upgrading into rare earth-based catalysts for catalytic degradation of VOCs not only provides new ideas for the sustainable utilization of rare earth resources, but also provides a more efficient solution for VOCs pollution control.
[0003] Chinese patent 104371555A discloses a method for recycling and regenerating waste polishing powder, which comprises mixing waste polishing powder with nitric acid, adding hydrogen peroxide to the bottom of the solution, heating and dissolving, and then using ammonia water to adjust the pH value and precipitate to obtain rare earth oxides. Chinese patent CN111471865A discloses a method for recycling waste rare earth polishing powder, which comprises using strong acid multi-stage countercurrent leaching, and then extracting and stripping to obtain a high-purity rare earth chloride solution. The above method is not only complex in process and consumes a large amount of chemical reagents, but also requires a special multi-stage countercurrent leaching device, which consumes water and energy and has high recovery costs.
[0004] To sum up, in view of the problems and defects in the existing technical processes for the recovery and reuse of rare earth elements in waste polishing powder, it is of great strategic significance to design and develop a method for recovering and reusing rare earth elements in waste polishing powder with high rare earth element recovery efficiency, low environmental pollution and good reuse effect. Summary of the invention
[0005] In order to overcome the shortcomings of the existing recycling technology of rare earth in waste polishing powder, the purpose of the present invention is to provide a method for mechanochemical enhanced deconstruction to recover rare earth in waste polishing powder and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs. The present invention first pre-treats the waste polishing powder by mechanochemical enhanced deconstruction, changes the chemical properties of the structural stability of the rare earth components in the waste polishing powder, and changes it from a difficult-to-immerse type to an easy-to-immerse type; then combines the mechanochemical enhanced deconstruction product with acid leaching extraction technology and complex salt precipitation technology to achieve efficient separation and purification of rare earth elements, and finally regenerates the La2O3 / CeO2 catalyst through a sacrificial template method and uses it for efficient catalytic degradation of VOCs. Thus, a process with mild reaction conditions, high economic benefits and strong universality is provided to achieve efficient recovery and upgrading of rare earth in waste polishing powder and realize its resource utilization.
[0006] A method for mechanochemically enhanced deconstruction and recovery of rare earth in waste polishing powder and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs, comprising the following steps:
[0007] (1) Mechanical and chemical enhanced deconstruction of waste polishing powder: Mix waste polishing powder, NaOH and deionized water, and use a high-energy ball mill to perform a mechanochemical reaction on the mixture. After the mechanochemical reaction is completed, rinse with deionized water and filter to obtain waste polishing powder deconstruction residue and filtrate 1. The reaction conditions for the mechanical and chemical enhanced deconstruction of waste polishing powder are as follows: the mass ratio of waste polishing powder to NaOH is 5:1 to 1:1 g / g, the mass ratio of waste polishing powder to deionized water is 5:1 to 1:1 g / g, the ball-to-material ratio is 1:5 to 1:25 g / g, the ball mill speed is 200 to 800 rpm, and the ball milling time is 1 to 6 hours.
[0008] (2) Acid leaching extraction of rare earth elements: The waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration. The acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 2 to 8 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:10 to 1:20 kg / L, the leaching temperature is 60 to 90°C, the leaching time is 1 to 6 hours, and the stirring rate is 200 to 600 rpm.
[0009] (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out and filtered to obtain CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2; then the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is reacted with NaOH solution, and after the reaction is completed, solid-liquid separation is carried out to obtain filtrate 3 and rare earth hydroxide, which are then reacted with dilute nitric acid solution to convert into a La(NO3)3 / Ce(NO3)4 mixed solution, and dried under low temperature conditions to obtain a La(NO3)3 / Ce(NO3)4 solid product. The reaction conditions for the double salt precipitation, separation and purification are as follows: the mass ratio of sodium sulfate to rare earth leaching solution is 100-200 g / L, the reaction temperature is 60-100°C, the reaction time is 10-90 minutes, the molar concentration of the dilute nitric acid solution is 0.1-1.0 mol / L, the mass concentration of the NaOH solution is 30%-50%, and the drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution is 60-100°C.
[0010] (4) Preparation of La2O3 / CeO2 catalyst by template method: A small amount of ethanol is added to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, and the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template are uniformly mixed and dried, and then calcined in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material. The La2O3 / CeO2 catalyst-loaded SiO2 composite material reacts with a NaOH solution to remove the SiO2 template, and the final product is separated by centrifugation, and the La2O3 / CeO2 catalyst is obtained after drying. The reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 1:1-4:1 g / g, the drying temperature of the mixture is 30°C-80°C, the calcination temperature is 600-900°C, and the insulation time is 1-4 hours; when removing the template, the molar concentration of the NaOH solution is 1-10 mol / L, the reaction temperature is 60-90°C, the reaction time is 24-72 hours, the centrifuge speed is 6000-10000 rpm, the centrifugation time is 5-10 minutes, and the drying temperature of the final product La2O3 / CeO2 catalyst is 30-80°C.
[0011] Compared with the existing recycling process of rare earth in waste polishing powder, the process of the present invention adopts mechanochemical enhanced deconstruction technology to quickly and easily change the physicochemical properties of rare earth components in waste polishing powder, reduce the reaction activation energy of rare earth component leaching and improve its leaching activity, so that the leaching rate of rare earth elements is greatly improved; and a high-activity La2O3 / CeO2 catalyst is prepared by regeneration using a sacrificial template method and used for catalytic degradation of VOCs. The present invention provides a technical process with mild reaction conditions, high rare earth recovery efficiency and high catalytic degradation efficiency of regenerated catalysts for VOCs, so as to achieve efficient recovery and high-quality recycling of rare earth in waste polishing powder. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 A flow chart showing a method for mechanochemically enhanced deconstruction and recovery of rare earths in waste polishing powder and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs. DETAILED DESCRIPTION
[0013] Example 1
[0014] Follow the steps below to process:
[0015] (1) Mechanical and chemical enhanced deconstruction of waste polishing powder: waste polishing powder, NaOH and deionized water are mixed, and the mixture is subjected to a mechanochemical reaction using a high-energy ball mill. After the mechanochemical reaction is completed, the mixture is rinsed with deionized water and filtered to obtain waste polishing powder deconstruction residue and filtrate 1. The reaction conditions for the mechanical and chemical enhanced deconstruction of waste polishing powder are as follows: the mass ratio of waste polishing powder to NaOH is 1:1 g / g, the mass ratio of waste polishing powder to deionized water is 2:1 g / g, the ball-to-material ratio is 1:15 g / g, the ball mill speed is 500 rpm, and the ball milling time is 2 hours.
[0016] (2) Acid leaching extraction of rare earth elements: The waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration. The acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 4 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:15 kg / L, the leaching temperature is 80°C, the leaching time is 3 hours, and the stirring rate is 600 rpm.
[0017] (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out and the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2 are obtained by filtration; the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is then reacted with a NaOH solution. After the reaction is completed, solid-liquid separation is carried out to obtain a filtrate 3 and a rare earth hydroxide, which is then reacted with a dilute nitric acid solution to be converted into a La(NO3)3 / Ce(NO3)4 mixed solution, and finally dried under low temperature conditions to obtain a La(NO3)3 / Ce(NO3)4 solid product. The reaction conditions for the double salt precipitation, separation and purification are as follows: the mass ratio of sodium sulfate to rare earth leaching solution is 200 g / L, the reaction temperature is 95°C, the reaction time is 30 minutes, the molar concentration of the dilute nitric acid solution is 1.0 mol / L, the mass concentration of the NaOH solution is 50%, and the drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution is 80°C.
[0018] (4) Preparation of La2O3 / CeO2 catalyst by template method: A small amount of ethanol is added to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, and the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template are uniformly mixed and dried, and then calcined in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material. The La2O3 / CeO2 catalyst-loaded SiO2 composite material reacts with a NaOH solution to remove the SiO2 template, and the final product is separated by centrifugation, and the La2O3 / CeO2 catalyst is obtained after drying. The reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 3:1 g / g, the drying temperature of the mixture is 60°C, the calcination temperature is 900°C, and the insulation time is 2 hours; when removing the template, the molar concentration of the NaOH solution is 2 mol / L, the reaction temperature is 80°C, the reaction time is 72 hours, the centrifuge speed is 6000 rpm, the centrifugation time is 10 minutes, and the drying temperature of the final product La2O3 / CeO2 catalyst is 60°C.
[0019] The ICP test results show that the recovery rate of rare earth lanthanum and cerium in waste polishing powder is about 99.2%. The regenerated La2O3 / CeO2 catalyst is used for the thermal catalytic degradation of styrene. The degradation test results show that the catalytic treatment efficiency of the obtained La2O3 / CeO2 catalyst for styrene can reach 99.3%.
[0020] Example 2
[0021] Follow the steps below to process:
[0022] (1) Mechanical and chemical enhanced deconstruction of waste polishing powder: waste polishing powder, NaOH and deionized water are mixed, and the mixture is subjected to a mechanochemical reaction using a high-energy ball mill. After the mechanochemical reaction is completed, the mixture is rinsed with deionized water and filtered to obtain waste polishing powder deconstruction residue and filtrate 1. The reaction conditions for the mechanical and chemical enhanced deconstruction of waste polishing powder are as follows: the mass ratio of waste polishing powder to NaOH is 1:1 g / g, the mass ratio of waste polishing powder to deionized water is 2:1 g / g, the ball-to-material ratio is 1:15 g / g, the ball mill speed is 500 rpm, and the ball milling time is 2 hours.
[0023] (2) Acid leaching extraction of rare earth elements: The waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration. The acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 4 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:15 kg / L, the leaching temperature is 60°C, the leaching time is 2 hours, and the stirring rate is 600 rpm.
[0024] (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out and the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2 are obtained by filtration; the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is then reacted with a NaOH solution. After the reaction is completed, solid-liquid separation is carried out to obtain a filtrate 3 and a rare earth hydroxide, which is then reacted with a dilute nitric acid solution to be converted into a La(NO3)3 / Ce(NO3)4 mixed solution, and finally dried under low temperature conditions to obtain a La(NO3)3 / Ce(NO3)4 solid product. The reaction conditions for the double salt precipitation, separation and purification are as follows: the mass ratio of sodium sulfate to rare earth leaching solution is 200 g / L, the reaction temperature is 80°C, the reaction time is 20 minutes, the molar concentration of the dilute nitric acid solution is 1.0 mol / L, the mass concentration of the NaOH solution is 50%, and the drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution is 80°C.
[0025] (4) Preparation of La2O3 / CeO2 catalyst by template method: A small amount of ethanol is added to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, and the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template are uniformly mixed and dried, and then calcined in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material. The La2O3 / CeO2 catalyst-loaded SiO2 composite material reacts with a NaOH solution to remove the SiO2 template, and the final product is separated by centrifugation, and the La2O3 / CeO2 catalyst is obtained after drying. The reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 2:1 g / g, the drying temperature of the mixture is 60°C, the calcination temperature is 900°C, and the insulation time is 2 hours; when removing the template, the molar concentration of the NaOH solution is 2 mol / L, the reaction temperature is 80°C, the reaction time is 72 hours, the centrifuge speed is 6000 rpm, the centrifugation time is 10 minutes, and the drying temperature of the final product La2O3 / CeO2 catalyst is 60°C.
[0026] The ICP test results show that the recovery rate of rare earth lanthanum and cerium in waste polishing powder is about 98.5%. The regenerated La2O3 / CeO2 catalyst is used for the thermal catalytic degradation of styrene. The degradation test results show that the catalytic treatment efficiency of the obtained La2O3 / CeO2 catalyst for styrene can reach 99.1%.
[0027] Example 3
[0028] Follow the steps below to process:
[0029] (1) Mechanical and chemical enhanced deconstruction of waste polishing powder: waste polishing powder, NaOH and deionized water are mixed, and the mixture is subjected to a mechanochemical reaction using a high-energy ball mill. After the mechanochemical reaction is completed, the mixture is rinsed with deionized water and filtered to obtain waste polishing powder deconstruction residue and filtrate 1. The reaction conditions for the mechanical and chemical enhanced deconstruction of waste polishing powder are as follows: the mass ratio of waste polishing powder to NaOH is 1:1 g / g, the mass ratio of waste polishing powder to deionized water is 2:1 g / g, the ball-to-material ratio is 1:15 g / g, the ball mill speed is 500 rpm, and the ball milling time is 2 hours.
[0030] (2) Acid leaching extraction of rare earth elements: The waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration. The acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 4 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:15 kg / L, the leaching temperature is 70°C, the leaching time is 2.5 hours, and the stirring rate is 600 rpm.
[0031] (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out and the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2 are obtained by filtration; the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is then reacted with a NaOH solution. After the reaction is completed, solid-liquid separation is carried out to obtain a filtrate 3 and a rare earth hydroxide, which is then reacted with a dilute nitric acid solution to be converted into a La(NO3)3 / Ce(NO3)4 mixed solution, and finally dried under low temperature conditions to obtain a La(NO3)3 / Ce(NO3)4 solid product. The reaction conditions for the double salt precipitation, separation and purification are as follows: the mass ratio of sodium sulfate to rare earth leaching solution is 200 g / L, the reaction temperature is 95°C, the reaction time is 30 minutes, the molar concentration of the dilute nitric acid solution is 1.0 mol / L, the mass concentration of the NaOH solution is 50%, and the drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution is 80°C.
[0032] (4) Preparation of La2O3 / CeO2 catalyst by template method: A small amount of ethanol is added to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, and the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template are uniformly mixed and dried, and then calcined in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material. The La2O3 / CeO2 catalyst-loaded SiO2 composite material reacts with a NaOH solution to remove the SiO2 template, and the final product is separated by centrifugation, and the La2O3 / CeO2 catalyst is obtained after drying. The reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 1:1 g / g, the drying temperature of the mixture is 80°C, the calcination temperature is 600°C, and the insulation time is 2 hours; when removing the template, the molar concentration of the NaOH solution is 2 mol / L, the reaction temperature is 80°C, the reaction time is 72 hours, the centrifuge speed is 6000 rpm, the centrifugation time is 10 minutes, and the drying temperature of the final product La2O3 / CeO2 catalyst is 60°C.
[0033] The ICP test results show that the recovery rate of rare earth lanthanum and cerium in waste polishing powder is about 98.7%. The regenerated La2O3 / CeO2 catalyst is used for the thermal catalytic degradation of styrene. The degradation test results show that the catalytic treatment efficiency of the obtained La2O3 / CeO2 catalyst for styrene can reach 99.8%.
[0034] Example 4
[0035] Follow the steps below to process:
[0036] (1) Mechanical and chemical enhanced deconstruction of waste polishing powder: waste polishing powder, NaOH and deionized water are mixed, and the mixture is subjected to a mechanochemical reaction using a high-energy ball mill. After the mechanochemical reaction is completed, the mixture is rinsed with deionized water and filtered to obtain waste polishing powder deconstruction residue and filtrate 1. The reaction conditions for the mechanical and chemical enhanced deconstruction of waste polishing powder are as follows: the mass ratio of waste polishing powder to NaOH is 1:1 g / g, the mass ratio of waste polishing powder to deionized water is 2:1 g / g, the ball-to-material ratio is 1:15 g / g, the ball mill speed is 500 rpm, and the ball milling time is 2 hours.
[0037] (2) Acid leaching extraction of rare earth elements: The waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration. The acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 4 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:15 kg / L, the leaching temperature is 90°C, the leaching time is 3 hours, and the stirring rate is 600 rpm.
[0038] (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out and the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2 are obtained by filtration; the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is then reacted with a NaOH solution. After the reaction is completed, solid-liquid separation is carried out to obtain a filtrate 3 and a rare earth hydroxide, which is then reacted with a dilute nitric acid solution to be converted into a La(NO3)3 / Ce(NO3)4 mixed solution, and finally dried under low temperature conditions to obtain a La(NO3)3 / Ce(NO3)4 solid product. The reaction conditions for the double salt precipitation, separation and purification are as follows: the mass ratio of sodium sulfate to rare earth leaching solution is 200 g / L, the reaction temperature is 100°C, the reaction time is 60 minutes, the molar concentration of the dilute nitric acid solution is 1.0 mol / L, the mass concentration of the NaOH solution is 50%, and the drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution is 80°C.
[0039] (4) Preparation of La2O3 / CeO2 catalyst by template method: A small amount of ethanol is added to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, and the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template are uniformly mixed and dried, and then calcined in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material. The La2O3 / CeO2 catalyst-loaded SiO2 composite material reacts with a NaOH solution to remove the SiO2 template, and the final product is separated by centrifugation, and the La2O3 / CeO2 catalyst is obtained after drying. The reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 2:1 g / g, the drying temperature of the mixture is 60°C, the calcination temperature is 900°C, and the insulation time is 2 hours; when removing the template, the molar concentration of the NaOH solution is 2 mol / L, the reaction temperature is 90°C, the reaction time is 72 hours, the centrifuge speed is 6000 rpm, the centrifugation time is 10 minutes, and the drying temperature of the final product La2O3 / CeO2 catalyst is 60°C.
[0040] The ICP test results show that the recovery rate of rare earth lanthanum and cerium in waste polishing powder is about 99.5%. The regenerated La2O3 / CeO2 catalyst is used for the thermal catalytic degradation of styrene. The degradation test results show that the catalytic treatment efficiency of the obtained La2O3 / CeO2 catalyst for styrene can reach 99.5%.
Claims
1. A method for mechanochemically enhanced deconstruction and recovery of rare earth in waste polishing powder and high-quality regeneration of La2O3 / CeO2 catalyst for catalytic degradation of VOCs, characterized in that: The specific steps are as follows: (1) Mechanical and chemical enhanced decomposition of waste polishing powder: waste polishing powder, NaOH and deionized water are mixed, and the mixture is subjected to a mechanochemical reaction using a high-energy ball mill; after the mechanochemical reaction, the mixture is rinsed with deionized water and filtered to obtain waste polishing powder decomposition residue and filtrate 1; the reaction conditions for the mechanical and chemical enhanced decomposition of waste polishing powder are: the mass ratio of waste polishing powder to NaOH is 5:1 to 1:1 g / g, and the mass ratio of waste polishing powder to deionized water is 5:1 to 1:1 g / g; (2) Acid leaching extraction of rare earth elements: the waste polishing powder decomposition residue obtained in step (1) is mixed with a hydrochloric acid solution, and an acid leaching reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and leaching residue and rare earth-containing leaching solution are obtained by filtration; the acid leaching reaction conditions are: the molar concentration of the hydrochloric acid solution is 2 to 8 mol / L, the solid-liquid ratio of the dried decomposition residue to the hydrochloric acid solution is 1:10 to 1:20 kg / L, the leaching temperature is 60 to 90° C., the leaching time is 1 to 6 hours, and the stirring rate is 200 to 600 rpm; (3) Precipitation, separation and purification of complex salts of rare earth elements: The rare earth-containing leaching solution obtained in step (2) is mixed with Na2SO4, and a rare earth complex salt precipitation reaction is carried out under heating and stirring conditions. After the reaction is completed, solid-liquid separation is carried out, and filtration is performed to obtain CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate and filtrate 2; then the CeNa(SO4)2 / LaNa(SO4)2 complex salt precipitate is reacted with NaOH solution, and after the reaction is completed, solid-liquid separation is carried out to obtain filtrate 3 and rare earth hydroxide, which are then mixed with dilute nitrate to obtain a filtrate 3. The acid solution is converted into a La(NO3)3 / Ce(NO3)4 mixed solution by reaction, and then dried to obtain a La(NO3)3 / Ce(NO3)4 solid product; the reaction conditions for the double salt precipitation separation and purification are: the mass ratio of sodium sulfate to rare earth leaching solution is 100-200 g / L, the double salt precipitation reaction temperature is 60-100°C, the double salt precipitation reaction time is 10-90 minutes, the molar concentration of the dilute nitric acid solution is 0.1-1.0 mol / L, and the mass concentration of the NaOH solution is 30%-50%; (4) Preparation of La2O3 / CeO2 catalyst by template method: Add ethanol to the La(NO3)3 / Ce(NO3)4 solid product obtained in step (3) to dissolve it, uniformly mix the La(NO3)3 / Ce(NO3)4 solid product, ethanol solution and mesoporous SiO2 template and dry them, then calcine them in a box furnace to form a La2O3 / CeO2 catalyst-loaded SiO2 composite material; react the obtained La2O3 / CeO2 catalyst-loaded SiO2 composite material with NaOH solution to remove the SiO2 template, separate the final product by centrifugation, and finally After drying, La2O3 / CeO2 catalyst is obtained; the reaction conditions for preparing La2O3 / CeO2 catalyst by the template method are as follows: the mass ratio of La(NO3)3 / Ce(NO3)4 solid product to mesoporous SiO2 template is 1:1-4:1, the calcination temperature is 600-900°C, and the insulation time is 1-4 hours; when removing the template, the molar concentration of the NaOH solution is 1-10 mol / L, the reaction temperature is 60-90°C, the reaction time is 24-72 hours, the centrifuge speed is 6000-10000 rpm, and the centrifugation time is 5-10 minutes.
2. The method according to claim 1, characterized in that: In step (1), the ball-to-material ratio is 1:5-1:25 g / g, the ball mill speed is 200-800 rpm, and the ball milling time is 1-6 hours.
3. The method according to claim 1, characterized in that The drying temperature of the La(NO3)3 / Ce(NO3)4 mixed solution in step (3) is 60-100°C.
4. The method according to claim 1, characterized in that: The drying temperature of the mixture in step (4) is 30-80°C.
5. The method according to claim 1, characterized in that The drying temperature of the final product La2O3 / CeO2 catalyst in step (4) is 30-80°C.
Citation Information
Patent Citations
Method for recovering rare metals of lanthanum, cerium and zirconium from smelting slag
CN108677024A
Method for gradient separation and recycle of rare earth in waste cerium-based rare earth polishing powder through two-step acid leaching
CN112725622A
Method for separating and extracting rare earth and regenerated rare earth polishing powder from waste rare earth polishing powder
CN112725623A
Method for mechanically activating and intensively leaching rare earth in waste polishing solution
CN114107668A
Method for recovering rare-earth in cerium-based rare-earth polishing powder waste by two-step acid leaching gradient separation
US20230265541A1